Bidirectional Interaction Between the Brain and Bone in Traumatic Brain Injury - Wei Zhang; Jun Zou; Lingli Zhang (Advanced Science)
Abstract Traumatic brain injury (TBI), which refers to damage caused by external forces to the brain, significantly affects systemic organs and tissues, especially bone homeostasis. An increasing number of studies have revealed bidirectional crosstalk between the brain and bone, and the interactions between these systems in the context of TBI remain unclear. Here, existing research on the relationship between the brain and bone is summarized to explore their interactions and underlying mechanisms in TBI. Clinical studies indicate that long‐term loss of bone mass and increased risk of osteoporosis occur in patients after TBI. Interestingly, the rate of bone healing is accelerated when patients with TBI also suffer from fractures, which then worsens the prognosis of TBI. The bidirectional effects and underlying mechanisms that connect TBI and bone through neurohormones, neuropeptides, neurotransmitters, and mechanical factors are reviewed. The promising applications of bone marrow mesenchymal stromal cells, their derived extracellular vesicles, and bone‐derived factors for TBI recovery are also elucidated. Strategies to prevent osteoporosis management and potential mechanisms to accelerate fracture healing after TBI are proposed based on the brain–bone axis, and results are expected to translate into a clinical scenario for TBI and bone disease.